Market Knowledge of SMEs in Business Online from the Perspective of Islamic Education - Sumitro Sarkum; Ade Parlaungan Nasution; Denny Ammari Ramadhan; Ajeng Handayani Purwaningrum (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The objective of this article is to analyze the effect of market knowledge on the performance of SMEs through engagement. This study explores marketing strategy and operational capability to run the role of the marketing function in achieving competitive advantage in the online business. This research uses quantitative methods with SEM analysis techniques. The population in this study is SMEs in Indonesia, with 178 as a sample. Data were collected by questionnaires. This study found establishing an engagement for mutual value creation and sustainability can improve business performance. The findings also resulted in a new discourse in management strategies in order to minimize the ability of SMEs to carry out marketing functions in online businesses. The outcomes show that Collective decision-making for the benefit of the company provides input on marketing strategies. This is in line with the perspective of Islamic education, which emphasizes business ethics, avoiding usury practices, and developing business owners with knowledge that is in accordance with the Islamic context.